Band-Pass Filter Microstrip at 3 GHz Frequency Using Square Open-Loop Resonator for S-Band Radar Applications - Rima Anisa Maulidini; M. Reza Hidayat; Teguh Praludi (National Research and Innovation Agency, 2020)
In telecommunication, filters are often used to pass the desired frequency. One of them is the Band-Pass Filter (BPF) which is passing signals between the upper cut-off frequency and the lower cut-off frequency. This research aims to make a band-pass filter that can pass 3 GHz frequency with a bandwidth of 200 MHz. This filter is designed with a square open-loop resonator simulated using Advanced Design System (ADS) software. The filter is made using FR 4-epoxy substrates with a dielectric constant (ε ) of 4.6 and substrate thickness (h) of 1.6 mm. Based on the simulation results obtained in the form of a comparison graph between the response of magnitude to frequency, it shows that the value of the return loss (S 11 ) parameter of -23.549 dB, insertion loss (S 21 ) parameter value of -1.397 dB, and a slightly shifted middle frequency of 2.890 GHz. Then for the measurement results obtained a parameter value return loss (S 11 ) of -16.364 dB, parameter value insertion loss (S 21 ) of -3.561 dB with a center frequency of 3.185 GHz.